Connection of Economy and Society with Environment (International Journal of Innovative Research in Engineering & Management, 2021)
Environment is equally as essential for human being as  economics but there are many limitations which are connected  with environment, when economy has given precedence over  the environment problems which is having negative impacts  on society. The environment is connected with the sustainable  development as it is essential to preserve the human and also  necessary to alter the attitude of the people for environment.  Sustainable development has been portrayed as a connection  between the environment, society and economy, therefore,  these three cannot be studied as a distinct entity. The  economics has given little bit importance when it comes to  politics and at the same time environment problems has given  lesser priority but this method is not appropriate in present  situation as economy is directly linked with the society and  human is dependent upon the environment. Thus, it is  essential to have an analysis of these three distinct entities in a  single frame and present paper’s strategy is to evaluate the  dependencies of these three on one another. The future scope  of the research is to take the initiative to preserve the  environment from potential threats like climate change etc.
Keywords: Development; Environment; Ecology; Growth; Society